PENERAPAN METODE BERNYANYI DALAM MENINGKATKAN HAFALAN ASMAUL HUSNA - Dede Fatchuroji (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2018)
Many teachers and the general public are still confused about distinguishing between children with mild intellectual disabilities with normal children in general, in fact there are different things that must be handled and served specifically for children with mild disabilities, they have significant intelligence below the average and accompanied by an inability in behavioral adaptation that arises during development. For mentally retarded children have academic barriers in such a way that the learning services require a modification of the curriculum that is appropriate to their specific needs and carried out new innovations in the learning method. The application of the singing method as an effort to improve or train them in memorization, the singing method is repeating by filling out the Asmaul Husna material through the singing lyrics. The contents of this article are about the classification of mental retardation which is viewed from various perspectives and the implementation of the singing method.